DISTRIBUTION AND GEOINFORMATION DATA OF SAND FISHES (GOBIONIDAE) IN THE FERGANA VALLEY WATER BASINS (Scientific journal of the Fergana State University, 2025)
Members of the family Gobionidae are widely distributed species in the water basins of the Fergana Valley, with Gobio lepidolaemus being an endemic species of the Fergana Valley water basins. This species is also found in other water basins in Uzbekistan and Kyrgyzstan. Pseudorasbora parva and Abbottina rivularis are invasive species that have arrived from the rivers of the Far East through various pathways and have now adapted to the aquatic environments of the valley. This article presents geoinformation data on the representatives of the Gobionidae family, the occurrences of their populations in water basins, and information regarding their distribution.